The Islamic Educational Philosophy of Tuan Guru Haji Musthafa Umar Abdul Aziz in His Book Al-Fawaid and Its Relevance to Contemporary Education - Husnul Yamil; Adi Fadli; Abdul Mujib (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study analyses the Islamic educational philosophy of TGH Musthofa Umar Abdul Aziz as set out in his book entitled Al-Fawa’id, as well as its relevance to the discourse on contemporary Islamic education policy in Indonesia. This study employs a qualitative approach using a literature review (library research) design, combined with empirical analysis through a case study at the Al Aziziyah Kapek Islamic Boarding School in West Lombok. Research data was obtained. The findings reveal that the educational philosophy presented in Al-Fawa’id emphasizes three key principles: (1) the integration of knowledge, ethics, and spirituality as the foundation of Islamic education; (2) a pedagogical relationship based on moral exemplarity between teacher and student; and (3) an educational orientation that aims not only to transmit religious knowledge but also to cultivate moral character and social responsibility. In institutional practice, these principles are reflected in pesantren educational models that combine classical Islamic scholarship with adaptive responses to contemporary educational demands. The case study of Al-Aziziyah Islamic boarding school demonstrates that the educational ideas articulated in Al-Fawa’id contribute to strengthening the epistemological identity of pesantren while simultaneously encouraging curricular innovation responsive to modern educational dynamics. From the perspective of Islamic education policy in Indonesia, the study suggests that the educational thought of TGH Musthofa Umar Abdul Aziz holds strategic relevance in the context of strengthening pesantren institutions following the enactment of Law Number 18 of 2019 on Pesantren. The concept of integrating knowledge and morality proposed in Al-Fawa’id may serve as an epistemological foundation for developing pesantren curricula that remain rooted in traditional Islamic scholarship while addressing contemporary educational challenges. This article therefore argues that revitalizing the educational thought of local Muslim scholars constitutes a crucial strategy for constructing a contextual and resilient model of Islamic education in modern Indonesia.